SAFETY CLIMATE AND SAFETY PERFORMANCE AMONG CONSTRUCTION WORKERS IN LANGKAWI ISLAND, MALAYSIA - Syazwan Syah Zulkifly; Nadiah Hanim Mohd Jun, (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
The construction sector is recognized for its hazardous working conditions, which have led to a multitude of accidents and fatalities. Consequently, ensuring safety within the construction industry remains a crucial concern for all involved parties. This research aimed to investigate the correlation between worker-centric safety climate and safety performance among construction employees in Langkawi. A survey was carried out among construction personnel in Langkawi, Malaysia, utilizing a questionnaire as the primary instrument for data collection. A total of 384 respondents were invited to partake in the study. The questionnaire encompassed queries pertaining to the influence of co-workers, employee attitudes, worker competence, and safety performance. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) software. The research discovered that the influence of co-workers, employee attitudes, and worker competence had a significant impact on safety performance among construction employees in Langkawi. The empirical evidence corroborated all six hypotheses examined in the research. This study concludes that a worker-centric safety climate is a vital element affecting safety performance within the construction sector. The influence of co-workers, employee attitudes, and worker competence were identified as significant determinants of safety performance among construction personnel in Langkawi. The study offers valuable insights for augmenting worker safety climate and enhancing safety performance in the construction industry.